Cultivating an Environment Inclusive of Students with Varying Developmental, Emotional, and Learning Needs - Alisha Ortiz; Victor R. Wilburn; Julie Ray; Melissa Odegard-Koester (Academic Chairpersons Conference Proceedings, 2020)
The learning needs of students today represent a unique shift in the way we think about student preparedness for the academic experience and our duty to create the optimal learning environment for them. This presentation provides different ways Department Chairs have led faculty to help students with varying needs find success in higher education.
Keywords: Disabilities; Accommodations; Mental Health